Dot1 and Histone H3K79 Methylation in Natural Telomeric and HM Silencing - Takahashi, Yoh-Hei (2011)
The expression of genes that reside near telomeres is attenuated through telomere position-effect variegation (TPEV). Using a URA3 reporter located at TEL-VIIL of S. cerevisiae, it was demonstrated that the disruptor of telomeric silencing-1 (Dot1) regulates TPEV by catalyzing the methylation of H3K79. URA3 was also used as a reporter to demonstrate that H3K79 methylation is required for HM silencing. Surprisingly, a genome-wide expression analysis of mutants defective in H3K79 methylation patterns indicated that only a few telomeric genes, such as the COS12 located at TEL-VIIL, are subject to H3K79 methylation-dependent natural silencing. Consistently, loss of Dot1 did not globally alter Sir2/3 occupancy in subtelomeric regions, but did lead to some telomere-specific changes. Furthermore, we demonstrated that H3K79 methylation by Dot1 does not play a role in the maintenance of natural HML silencing. Our results show that the commonly used URA3 reporter located at TEL-VIIL or at the mating loci may not report on natural PEV and that studies concerning the epigenetic mechanism of silencing in yeast should employ assays that report on the natural pattern of gene expression.